Lebanon : Teachers - World Bank (Washington, DC, 2014)
In 2009, Lebanon spent 1.8 percent of Gross domestic product (GDP) on public education. In the same year, as a percentage of total government expenditure, Lebanon spent 7.2 percent on education. An important challenge for Lebanon is that its best-trained people migrate abroad or have to face low rates of return to schooling domestically. Lebanon is experiencing an over-supply of teachers, which provides an opportunity to be more selective and raise the bar for entering teachers. While some neighboring countries only screen teacher candidates based on test scores in the secondary school leaving examination (West Bank & Gaza, Jordan, and Yemen), applicants for teacher education programs in Lebanon are admitted based on two criteria: (i) test scores in the secondary school leaving examination, and (ii) performance in the compulsory entrance examination for teacher education programs. While there are some mechanisms in place to hold teachers accountable, their enforceability is limited. Teachers are offered few financial incentives or opportunities for public recognition to reward strong performance. There is no probationary period prior to awarding open-ended status. While the first years of teaching are among the best available predictors of a teacher's performance later on in their career, Lebanon does not use this period to weed out the lowest-performing teachers. Once a teacher has an open-ended appointment, weak results in the performance evaluation process may not be used to dismiss ineffective teachers. In fact, based on the evaluation process, it appears to be difficult to identify low-performers and high performers. Lebanon may look to the experience of other countries in setting policies to remove chronically low-performing teachers. The benefits of doing so are twofold: first, such mechanisms protect students from the detrimental and lasting effects of having poor teachers; and second, they can give teachers a clear incentive to work hard in order to avoid them.